2022
DOI: 10.1364/oe.458367
|View full text |Cite
|
Sign up to set email alerts
|

Three-axis closed-loop optically pumped magnetometer operated in the SERF regime

Abstract: We propose a three-axis closed-loop optically pumped magnetometer with high sensitivity. The closed-loop magnetometer has a three-axis sensitivity of approximately 30 fT/Hz1/2 using two orthogonal laser beams for pumping and probing the alkali metal atoms. In the closed-loop mode, the dynamic range is improved from ±5 nT to ±150 nT. The bandwidth is increased from about 100 Hz to over 2 kHz with 10 kHz modulation fields in x- and y-axes and another 6 kHz modulation field along the z-axis. Compared with single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…With operating parameters same as above simulation conditions, the bandwidths of triaxial magnetic detection are 92 Hz, 92 Hz, and 100 Hz, as Figure 7 shows. According to our previous research [14,25,26], highfrequency and large amplitude modulated magnetic field would bring about high bandwidth of the zero-field OPM. Thus, we set transverse rotationally modulated magnetic field at 6 kHz, with 2000 nT pp amplitude, and longitudinal modulated magnetic field at 9 kHz, with the same 2000 nT pp amplitude.…”
Section: Closed-loop Operationmentioning
confidence: 97%
See 2 more Smart Citations
“…With operating parameters same as above simulation conditions, the bandwidths of triaxial magnetic detection are 92 Hz, 92 Hz, and 100 Hz, as Figure 7 shows. According to our previous research [14,25,26], highfrequency and large amplitude modulated magnetic field would bring about high bandwidth of the zero-field OPM. Thus, we set transverse rotationally modulated magnetic field at 6 kHz, with 2000 nT pp amplitude, and longitudinal modulated magnetic field at 9 kHz, with the same 2000 nT pp amplitude.…”
Section: Closed-loop Operationmentioning
confidence: 97%
“…Conventional zero-field OPMs measure the magnetic field along the transverse one or two directions perpendicular to the pump direction and are difficult to realize the simultaneous and independent measurement of the triaxial magnetic fields [1,9,10]. To achieve triaxial measurement, some research groups adopted a dual-beam configuration, either pump-probe [11,12], or dual-pump/ probe scheme [13,14]. This scheme complicates the structure of the magnetometer, which in turn increases the sensor's volume and complexity, and is not beneficial for its development into an arrayed wearable system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circular component of the light creates relatively uniform spin polarization, and the linear component is used to measure optical rotation generated by the atoms. The following is the Bloch equation describing the polarization state of atoms in the cell [ 24 , 25 , 26 , 27 , 28 ]: where is an atomic polarization state. is the slowing-down factor.…”
Section: Serf Ammentioning
confidence: 99%
“…Theoretical and experimental studies showed that the SERF magnetometer which can provide complete three-axis vector magnetic field information will help to improve the performance of the OPM-MEG system [111,112]. Tang et al put forward a variety of schemes to realize the three-axis magnetic field vector measurement of the SERF magnetometer, which will promote a large number of applications of the three-axis SERF magnetometer in the OPM-MEG system [113,114]. Frontiers in Physics frontiersin.org…”
Section: Biomedicinementioning
confidence: 99%